A LITERATURE REVIEW: IMPLEMENTATION OF SEXUAL EDUCATION FOR CHILDREN WITH SPECIAL NEEDS IN INDONESIA - Nurhikma, Andi; Hendriani, Wiwin (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2024)
Sexual education is one of the preventive measures to protect children with special needs from sexual violence. However, this program has not received much attention and still has challenges in its implementation in Indonesia. This study aims to explore the implementation of sexual education for children with special needs in Indonesia. This research method uses a literature study by collecting research articles to be reviewed and analyzed. Based on the search results on two databases, namely google scholar and web of science, 12 articles were obtained that met the criteria with 7 qualitative studies, 4 experimental studies and 1 cross-sectional study. Data analysis in this literature study used narrative synthesis analysis. Based on the results of the analysis, the research findings were categorized into four categories, namely 1) the effectiveness of sexual education, 2) teaching content, methods and media, 3) supporting factors, and 4) implementation constraints. Overall, the research article shows that the implementation of sexual education in Indonesia is still inadequate so an evaluation of the policy and curriculum is needed.